(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores the theoretical and practical foundations of using a multi-discrete (multi-subject) approach to enhance environmental education in higher education. The multi-discrete approach involves integrating environmental knowledge and skills with various disciplines such as biology, geography, physics, chemistry, computer science, arts, and technology. Such interdisciplinary integration fosters ecological awareness, critical thinking, and responsibility among students, while promoting the principles of sustainable development. The study analyzes the impact of interdisciplinary teaching methods on learning effectiveness and proposes practical recommendations for implementation in educational settings